The Use of Personal Vocabulary Notes Technique to Enhance Students' Writing Skill At Lakidende University - Ikosusilowati Ikosusilowati; Umar Umar (Universitas Cokroaminoto Palopo, 2021)
This research aims at investigating the current level of students’ writing skill before and after applying Personal Vocabulary Notes technique. The research problem was to know how Personal Vocabulary Notes Technique used to enhance students’ writing skill at Lakidende University. This research was used Experimental method is a quantitative research method used to determine the effect of independent variable on the dependent variable. This research applied pre-experimental design which one group in given pre test and post test. The instrument of this research is writing tasks which were taken during the treatment. The purpose of using these written products provides the data in term of organization, vocabulary, and language use. The population of this research was all of the fourth semester at Lakidende University who enrolled in academic year 2020/2021.The samples of this study were 26 students which were taken by using purposive sampling. But, the running of these research, they were only 21 Students was active. The result shows that the calculated t value (df=20) was bigger than the t table value (1.724), p value < 0.05, therefore it can be concluded that there was a difference in the students’ writing skill scores after being given Personal Vocabulary Notes technique, with an effect size of 1.613 or 94, 5% (Large effect). Based on the estimated mean value between pre post and post test, it was also known that there was an increase in student’s writing skill after used Personal Vocabulary Notes Technique. Means that, Ha was accepted and Ho was rejected.